Clinical features of pneumatosis intestinalis induced by alpha- glucosidase inhibitor in patients with type 2 diabetes mellitus: a single center retrospective study - Guanlin Wu; Weiheng He; Huimin Rao; Lin Lu; Xinran He; Xuewen Hou (Frontiers in Endocrinology)
PurposePneumatosis intestinalis (PI) is a rare but significant side effect associated with the use of alpha-glucosidase inhibitor (αGI) in the treatment of diabetes. This study aims to analyze the clinical features of PI induced by αGIs in patients with type 2 diabetes mellitus.MethodsWe conducted a retrospective analysis of patients diagnosed with PI between January 2018 and December 2023. Data collected included demographic characteristics, clinical symptoms and signs, laboratory findings, imaging results, endoscopic manifestations, treatments, and outcomes. Clinical characteristics were compared between patients who used acarbose and those who did not.ResultsA total of 48 patients with PI were included in the study, of whom 22 had used acarbose and 26 had not. The acarbose taken group was significantly older than the acarbose untaken group. Additionally, the prevalence of coronary heart disease and hypertension was markedly higher in patients taking acarbose. Importantly, total bilirubin levels were lower in those with PI who were on acarbose therapy.ConclusionOur findings highlight the need for increased vigilance regarding the potential development of PI in older diabetic patients with cardiovascular conditions following αGI administration. Timely intervention is crucial to prevent adverse outcomes. This study offers valuable insights for the future management of αGI in diabetes treatment.